Can the Bacterial Community of a High Arctic Glacier Surface Escape Viral Control? - Rassner, Sara M. E.; Anesio, Alexandre M.; Girdwood, Susan E.; Hell, Katherina; Gokul, Jarishma K.; Whitworth, David E.; Edwards, Arwyn (Frontiers in Microbiology, 2016)
Glacial ice surfaces represent a seasonally-evolving three-dimensional photic zone which accumulates microbial biomass and potentiates positive feedbacks in ice melt. Since viruses are abundant in glacial systems and may exert controls on supraglacial bacterial production, we examined whether changes in resource availability would promote changes in the bacterial community and the dynamics between viruses and bacteria of meltwater from the photic zone of a Svalbard glacier. Our results indicated that, under ambient nutrient conditions, low estimated viral decay rates account for a strong viral control of bacterial productivity, incurring a potent viral shunt of a third of bacterial carbon in the supraglacial microbial loop. Moreover, it appears that virus particles are very stable in supraglacial meltwater, raising the prospect that viruses liberated in melt are viable downstream. However, manipulating resource availability as dissolved organic carbon, nitrogen and phosporous in experimental microcosms demonstrates that the photic zone bacterial communities can escape viral control. This is evidenced by a marked decline in virus-to-bacterium ratio concomitant with increased bacterial productivity and number. Pyrosequencing shows a few bacterial taxa, principally Janthinobacterium sp., dominate both the source meltwater and microcosm communities. Combined, our results suggest that viruses maintain high virus-to-bacterium ratios to promote contact with low-density hosts, by the manufacture of robust particles, but that this necessitates a trade-off which limits viral production. Consequently, dominant bacterial taxa appear to access resources to evade viral control. We propose that a delicate interplay of bacterial and viral strategies affects biogeochemical cycling upon glaciers and, ultimately, downstream ecosystems.